Rastros e breves olhares da arte medieval na arquitetura eclesiástica sergipana - Costa, Orlando Pereira (2022)
This article aims to understand the elements that characterize the Romanesque and Gothic artistic styles during the Middle Ages and, through this analysis, seeks to investigate the permanence of these art styles in Brazilian architecture, more specifically in the sacred architecture of Sergipe. In this way, a problematization of the impacts generated from the introduction of these artistic styles is made, showing their functionality and their adhesion in society, as well as the meanings and pretensions that these constructions carry. In addition, there is also the intention of showing how these architectural styles assumed the function of establishing a form of communication between man and the sacred and between the clergy and society, in this way the reminiscences of these art styles that are still present will be presented. in contemporaneity.